Carl$1 (Bs birthday s - Day, Alexandra (New York : Farrar, Straus and Giroux, 1995)
Carl the rottweiler and the toddler in his care watch the preparation for Carl$1 (Bs surprise birthday party.s
Keywords: Surprise birthday parties -- Juvenile fiction; Dogs -- Juvenile fiction; Dogs -- Fiction; Birthdays -- Fiction